The new population problem : why families in developed countries are shrinking and what it means - Booth, Alan, 1935-2015; Crouter, Ann C. (Lawrence Erlbaum Asociates, 2005)
This book is based on the presentations and discussions from a national symposium on "Creating the Next Generation: Social, Economic, and Psychological Processes Underlying Fertility in Developed Countries," held at the Pennsylvania State University in 2003.
Keywords: Family size -- Developed countries -- Congresses.; Fertility, Human -- Developed countries -- Congresses.; Familles -- Dimension -- Pays industrialisés -- Congrès.; Fécondité humaine -- Pays industrialisés -- Congrès.; SOCIAL SCIENCE -- Demography.; Family size; Fertility, Human; Developed countries; Electronic book.; Conference papers and proceedings